2018
DOI: 10.22159/ajpcr.2018.v11i8.27791
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polyherbal With Antioxidant Activity

Abstract: Objective: The objective of this research was to develop a polyherbal formulation (PHF) using four different herbs and to evaluate their phytochemicals, physical constants, and determination of their antioxidant activity by DPPH method.Methods: The PHF authenticated herbs were characterized by studying its morphological and pharmacognostic characters. Phytochemical screening showed the presence of alkaloids, glycosides, carbohydrates, amino acid, tannin, steroids, and flavonoids in the combination extract. Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The redox potential of the OH groups of flavonoids gives them the ability to transfer a proton and/or an electron, thus trapping the free radicals. The antiradical strength of our formulations corroborates with the studies of Deepak and Anurekha and Anurekha, 38 who had already shown that the combination of 4 extracts of plants had antiradical activities against DPPH. Kabilan et al 39 also showed the same effects with their polyherbal formulation, while Chanthasri et al 40 showed the antiradical activities against DPPH and ABTS of 20 polyherbal formulations.…”
Section: Discussionsupporting
confidence: 90%
“…The redox potential of the OH groups of flavonoids gives them the ability to transfer a proton and/or an electron, thus trapping the free radicals. The antiradical strength of our formulations corroborates with the studies of Deepak and Anurekha and Anurekha, 38 who had already shown that the combination of 4 extracts of plants had antiradical activities against DPPH. Kabilan et al 39 also showed the same effects with their polyherbal formulation, while Chanthasri et al 40 showed the antiradical activities against DPPH and ABTS of 20 polyherbal formulations.…”
Section: Discussionsupporting
confidence: 90%
“…Maximum PM 10 concentrations during winter may result from combustion with favorable climatic conditions leading to lower boundary layer height, low wind speed resisting diffusion, and staying up of pollutants for a longer duration. [7,69] Heavy rains during monsoon washes out the pollutants reducing particle concentrations in the region. [70] During summer, temperature inversion occur leading to pollution accumulation.…”
Section: Pm 10 Variationmentioning
confidence: 99%
“…To help the usage of selected plant extracts within the conventional system of medicine, the antioxidant capability of the rhizome of Asparagus racemosus, the bark of Bauhinia variegata, seed kernel of Caesalpinia bonducella, the bark of Saraca asoka, and hardwood of Symplococus racemosus was examined. 3 In the current study, five different herbal plants were chosen for the preparation of polyherbal formulation and standardization in terms of macroscopical, physicochemical, qualitative, and quantification of bioactive constituents. All the individual plant extract and the polyherbal formulation were subjected to GC-MS analysis to consider the phytocompounds present and the evaluation of antioxidant activity was studied by the DPPH, radical scavenging, and hydrogen peroxide assay.…”
Section: Introductionmentioning
confidence: 99%